1972
DOI: 10.1002/ar.1091740206
|View full text |Cite
|
Sign up to set email alerts
|

Surface patterns in the reproductive tracts of the rabbit observed by scanning electron microscopy

Abstract: The ultrastructure of cell surface and tissue organization of reproductive tracts of female rabbits were observed by scanning electron microscopy. In the vagina, straight and shallow longitudinal folds were observed. Complex, very deep, narrow folds with small crypts were observed in the cervix uteri. Two types of cells were recognized : ciliated cells and secretory non-ciliated cells. The internal 0s area contained more ciliated cells than the external 0s area. In the uterus, two different patterns of fold fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 12 publications
5
6
0
Order By: Relevance
“…The SEM studies revealed an increase in secretory activity the first few days after ovulation, consistent with the secretory patterns reported previously for uterine proteins [2,15,22,23], but differences between P 4 -treated and control animals was small. However, the fact that the oviductal secretory cells appeared to be more active in the P 4 -treated does could indicate that some of the early increase in uterine proteins [2,22,23] may result from possible drainage of oviductal fluids into the uterus at the time of embryo passage.…”
Section: Experiments 1: Embryos Cultured In Uterine Proteinssupporting
confidence: 90%
See 4 more Smart Citations
“…The SEM studies revealed an increase in secretory activity the first few days after ovulation, consistent with the secretory patterns reported previously for uterine proteins [2,15,22,23], but differences between P 4 -treated and control animals was small. However, the fact that the oviductal secretory cells appeared to be more active in the P 4 -treated does could indicate that some of the early increase in uterine proteins [2,22,23] may result from possible drainage of oviductal fluids into the uterus at the time of embryo passage.…”
Section: Experiments 1: Embryos Cultured In Uterine Proteinssupporting
confidence: 90%
“…Blood P 4 is elevated by P 4 administration [23], and P 4 stimulates secretion by the secretory cells of the uterus, as indicated by transmission electron microscopy [4,8], and by secretion of uterine proteins [2,15,22,23]. The SEM studies revealed an increase in secretory activity the first few days after ovulation, consistent with the secretory patterns reported previously for uterine proteins [2,15,22,23], but differences between P 4 -treated and control animals was small.…”
Section: Experiments 1: Embryos Cultured In Uterine Proteinssupporting
confidence: 87%
See 3 more Smart Citations